2019
DOI: 10.1038/s41598-019-52921-z
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 3 deficiency does not impede digit regeneration in mice

Abstract: The mitochondrial deacetylase sirtuin 3 (SIRT3) is thought to be one of the main contributors to metabolic flexibility–promoting mitochondrial energy production and maintaining homeostasis. In bone, metabolic profiles are tightly regulated and the loss of SIRT3 has deleterious effects on bone volume in vivo and on osteoblast differentiation in vitro. Despite the prominent role of this protein in bone stem cell proliferation, metabolic activity, and differentiation, the importance of SIRT3 for regeneration afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…Sirt3 appears dispensable in a number of other in vivo processes 25‐26,47 . One study showed that loss of Sirt3 had no identifiable effect on innate immune responses and host defense against bacterial and fungal infections 25 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sirt3 appears dispensable in a number of other in vivo processes 25‐26,47 . One study showed that loss of Sirt3 had no identifiable effect on innate immune responses and host defense against bacterial and fungal infections 25 .…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that loss of Sirt3 had no identifiable effect on innate immune responses and host defense against bacterial and fungal infections 25 . Moreover, in response to bone injury, loss of Sirt3 had no impact on bone regeneration 26 while vascular atherosclerotic burden was not exacerbated by deleting Sirt3 in a mouse model of atherosclerosis 47 . In conclusion, our findings add to this growing list and show that oocyte developmental competence and female fertility remain intact following loss of Sirt3 under basal conditions and HFD‐induced obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NAD + -dependent sirtuin-3 (Sirt3) is the primary mitochondrial protein deacetylase and plays a critical role in mitochondrial quality control, including mitochondrial biogenesis, mitochondrial dynamics, and mitophagy-all of which are affected in age-related metabolic diseases (8)(9)(10)(11). Earlier work aiming to elucidate the role of Sirt3 in bone has produced conflicting results with some studies suggesting that Sirt3 is critical for skeletal homeostasis (12,13) while others found no physiological role of Sirt3 in bone (14,15). Sex steroid deficiency, aging, and inflammation cause an increase in osteoclast numbers and thereby bone loss (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…Methods of dual thresholding, 3D adaptive thresholding, genetic algorithms (Buie et al, 2007;Janc et al, 2013;Zhang et al, 2010), and shape recognition using deep learning techniques (Ambellan et al, 2019;Spampinato et al, 2017) have been used for segmentation of regions of interest. Regenerative outcomes in the mouse digit regeneration model have been largely quantified using µCT techniques coupled with ImageJ (Rasband, 1997), focusing on parameters such as length changes (Dawson et al, 2017), trabecular spacing, trabecular thickness, and volumetric change (Busse et al, 2019;Fernando et al, 2011;Sammarco et al, 2015;Sammarco et al, 2014;Simkin et al, 2017). Beyond micro-CT imaging, approaches such as DXA, CT, and MRI are also widely used for assessing bone mineral density and aspects of morphology.…”
Section: Introductionmentioning
confidence: 99%